Pengaruh Terapi Pijat Refleksi Telapak Kaki terhadap Perubahan Tekanan Darah pada Penderita Hipertensi di Desa Gue Gajah Kecamatan Darul Imarah - Qasthallani Qasthallani; Yadi Putra; Ellyza Fazlylawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a major factor contributing to high mortality rates and is often identified as the silent killer. Various non-pharmacological interventions have been developed to help lower blood pressure, such as the use of acupressure, herbal remedies, relaxation breathing exercises, meditation, aromatherapy, and reflexology on the soles of the feet. The focus of this study is to examine the effects of reflexology on the soles of the feet on blood pressure dynamics in individuals with hypertension in Gue Gajah Village, Darul Imarah District. The methodology applied was quantitative research with a quasi-experimental design, and the data collection pattern was a single group with pre- and post-treatment measurements (one group pretest-posttest). From a total of 328 hypertensive patients in the area, 15 research participants were purposively selected as samples. The study process took place from May 2 to 28, 2025. The results of the analysis using a paired t-test showed a significant change in blood pressure between before and after the foot reflexology treatment, both in systolic pressure (p-value = 0.000; p < 0.05) and diastolic pressure (p-value = 0.000; p < 0.05). Based on these findings, it can be stated that foot reflexology massage therapy has an effect on lowering blood pressure in hypertensive patients. These findings are expected to serve as a reference for health workers to expand the use of non-pharmacological interventions in the management of hypertension and open opportunities for further research with larger sample sizes and designs.